METAFORA DALAM LIRIK LAGU ANGGUN C SASMI - Bahanuddin, Sofianti; Hasbullah, Hasbullah (Universitas Hasanuddin, 2017)
This research aims to analyze the use of metaphorical language styles in songs. Because like poetry, the language used in the song is not the same as the language used when someone is conversing, often the language used in song lyrics is ambiguous and uses the style of the language. Based on this, the researchers are interested to discuss the use of language styles in song lyrics, but in this research, researchers focused on researching only on the style of metaphorical language with the title